Al-Tafsīr al-Yasāri (Tafsir Tematik Revolusioner Hassan Hanafi) Misbakhudin - Misbakhudin, Misbakhudin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
The aim of this paper is to describe Hassan Hanafi's thoughts in the discourse of the Qur'an and its exegeses. This study focus on Hassan Hanafi's ideas around thematic exegeses (maudhu'iy), which aim to complete the emptiness in the tahlily method that is not in accordance with the substance and needs of the people today. The method of tahlily now also makes the reader unable to identify his own reading. This makes the reading cool, useless, and absolute. Meanwhile, the people need a lively and useful exegesis, as well as a knowledge that are in accordance with their circumstances. Hassan's ideas in his works were analysed using a content analysis approach, which the author formulated in a title that was quite familiar with Hassan Hanafi himself, namely al-Tafsir al-Yasari. In his thematic exegesis (hermeneutics), Hassan Hanafi used Al-Qur'an as the main source. Based on the Qur'an, Hassan Hanafi seeks to describe humans and the social interrelations among them. Other things that are also misjudged relate to the position of humans in history, their ability to build social and political systems, and to propose alternatives through methods of analysing experiences that lead to the meaning of the text and even to reality itself.